A Global Assessment Tool for Reduction of CO2 Emissions Associated with Portland Cement and Relevant Sectors - Khalil, Esraa Ahmed Sayed Mohamed (AUC Knowledge Fountain, 2025)
The cement industry is key in the global construction development taking place, yet it contributes to environmental drawbacks, particularly global warming. Cement production is estimated to be responsible for 8% of the global CO2 emissions. There are global efforts to reduce the CO2 emissions associated with cement production. In addition to CO2 emissions, cement plants contribute to environmental dilapidation, poor air quality, and public health problems through NOx, Sox, and particulate matters emissions. Cement production is an intensive energy process, fossil fuel and raw materials consumer. Therefore, there are some challenges facing the cement industry to implement sustainable measures in its manufacturing processes and products. Evaluating the sustainability of cement plants and their manufacturing process is becoming a necessity. For that, an assessment framework for effectively identify, assess, categorize, and rate the most applicable CO2 improvement measure is proposed. This work has three correlated parts. The first part is the proposed set of improvement measures, based on the 5Cs approach for decarbonizing the cement industry and the sustainability pillars, for evaluating the sustainability of cement plants. These measures should represent a roadmap to CO2 reduction potentials considering the materials and energy streams within the cement production process. The concept of “Cleaner production” was used as a supporting theoretical concept for the logical flow of the measures. The measures were prioritized based on the hierarchy process and by integrating the industry and academic experts’ opinions. The second part is the building of an assessment model, using software tool, to evaluate and rate the implementation level of each improvement measure in cement plants. Through a structured yet flexible model each measure was evaluated based on assessment questions that are given significance factors and percentages compiled by the industry surveys, experts, site visits, and literature. A score for each measure is computed by the tool and is reflected in the overall cement plant score. The model is automated to formulate the results in a color-coded rating system. Furthermore, the third part is the application of the assessment tool on two major international cement plants operated also in Egypt. The results from the two cement plants provide insights about the most implemented CO2 reduction measures and the ones that need further implementation. Both plants’ have applied some sustainability measures and advancements in the industry that are reflected in the overall plants scores. Additionally, plant A computed overall score is 3.315, and plant B score is 3.441. The results are promising for the implementation level of CO2 improvement measures for both plants. The assessment tool facilitates the decision-making and investments allocations through prioritizing the scores of each measure. However, the transition of the cement industry towards net-zero emissions by 2050 requires continuous innovation, capital investments, regulation support, and global collaboration.